Agricultural price policy in India / by A. S. Kahlon and D. S. Tyagi - "Kahlon, A.S." (New Delhi, 1983)
Agricultural price intervention has been a common component of economic management policy in both developed an developing countries. However, the mature and the developing economies have very little in common in economic,social and institutional structures. It is the only with respect to the price theory that there are some common elements in the books and the material produced both in the developing and the developed countries.
Keywords: Agricultural price-India